Contribución del epifitismo accidental a la distribución de especies de plantas vasculares en un bosque templado lluvioso - Guzmán-Marín, Rosario; Saldaña, Alfredo (Gayana Botánica, 2017)
In a Valdivian forest stand, we identified vascular plant species occurring as accidental epiphytes, and we determined the contribution of accidental epiphytism on their local abundance. Four species were found as accidental epiphytes, being the fern Blechnum mochaenum the species showing the higher abundance proportion as accidental epiphyte (40%). Unexpectedly, individuals of this species occurring as accidental epiphytes did not differ in functional traits related to nutrient availability (LMA-leaf mass ratio- and leaf C/N ratio) from those that usually occur on the forest ground. As a shade tolerant and slow growing species, B. mochaenum apparently is not affected by the environmental restrictions of the epiphytic habitat.